Influence of Civic Education on the Development of Moral Reasoning and Prosocial Behaviour among Secondary School Students in Zamfara State, Nigeria - Sule Muhammad; Sani Ahmadu Gurjiya (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2026)
This study investigated the influence of civic education on the development of moral reasoning and prosocial behaviour among secondary school students in Zamfara State, Nigeria. Specifically, it examined the effect of civic education on students’ moral reasoning, its influence on prosocial behaviour, and the relationship between moral reasoning and prosocial behaviour. A descriptive correlation survey research design was employed, and a total of 384 students were selected using a simple random sampling technique. Data were collected using a structured questionnaire titled Civic Education, Moral Reasoning, and Prosocial Behaviour Questionnaire (CEMRPBQ), which was validated by experts and demonstrated high reliability with a Cronbach’s alpha of 0.89. Responses were measured on a five-point Likert scale. Data analysis involved descriptive statistics to summarize respondents’ perceptions and inferential statistics, including multiple regression and Pearson correlation, to test the research hypotheses. The findings revealed that civic education significantly enhances moral reasoning (β = 0.643, p < .001) and prosocial behaviour (β = 0.611, p < .001) among students. Furthermore, a strong positive relationship was observed between moral reasoning and prosocial behaviour (r = .712, p < .01), indicating that higher levels of moral reasoning are associated with increased prosocial tendencies. The study concluded that civic education plays a critical role in promoting ethical cognition and socially responsible behaviours among adolescents. It is recommended that schools adopt structured civic education programs, and teachers employ participatory teaching methods to reinforce moral and prosocial development in students.